2013
DOI: 10.1016/j.jcma.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes in lung cancer presenting as ground-glass opacities of 3 cm or less: A review of 5 years' experience

Abstract: The percentage of malignancy is high in pulmonary GGOs. Surgery results in an excellent prognosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The presence of a pure solid nodule independently predicted IAC with an AUC of 0.812, and patients with a pure solid nodule had a worse survival rate than did those with a pGGO or mGGO tumour. In agreement with our results, several studies found that the proportion of GGO areas relative to the total tumour area strongly predicted overall survival in patients with clinical T1N0M0 lung adenocarcinoma [29, 30]. Although our study shows that GGO is useful for diagnosing and predicting the prognosis of the adenocarcinoma subtypes, other factors should be identified to improve sensitivity and specificity, especially for mGGO tumours owing to their high recurrence rate [29].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of a pure solid nodule independently predicted IAC with an AUC of 0.812, and patients with a pure solid nodule had a worse survival rate than did those with a pGGO or mGGO tumour. In agreement with our results, several studies found that the proportion of GGO areas relative to the total tumour area strongly predicted overall survival in patients with clinical T1N0M0 lung adenocarcinoma [29, 30]. Although our study shows that GGO is useful for diagnosing and predicting the prognosis of the adenocarcinoma subtypes, other factors should be identified to improve sensitivity and specificity, especially for mGGO tumours owing to their high recurrence rate [29].…”
Section: Discussionsupporting
confidence: 91%
“…Six studies did not provide CT slice thickness while the remaining 21 studies reported CT slices from 0.5 to 3.0 mm. Time from the initial identification of the PSN to diagnosis and resection was given in only 1 of the 27 studies [57]. Tumour size was an inclusion criterion in all but two articles [56, 61].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 listed groups, 13 reported DFS/RFS [54, 57, 59, 60, 6466, 71, 72, 76, 78, 80, 81], 100% for 7 groups (345 patients) and ranged from 96.3% to 98.7% for another 6 groups (1507 patients). Among the 13 groups reporting OS [5557, 59, 60, 6365, 68, 69, 74, 78, 81], 2 (60 patients) reported an OS of 100% and 11 (1727 patients) reported OS rates ranging from 94.7% to 98.9%. One group of 23 patients had an LCS of 95.7% [55].…”
Section: Resultsmentioning
confidence: 99%
“…This group of tumors are correlated with a favorable prognosis after surgical resection. However, evidence suggests that other more invasive, non-lepidic growth patterns of adenocarcinoma such as acinar and papillary have presented as GGO nodules (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%